Participatory Management Model for the Creation of Equality and Equality in Education of Elementary Schools in Lower Central of Thailand - Samahito , Phra Khru Palad Chaiwat; Utairat, Weerawat (Journal of Education Studies, Chulalongkorn University, 2020)
The objective of this research was to creat a participatory management model for the creation of equality and equity in education of elementary schools in the lower central region of Thailand. The research population was 606 element schools. Research tools included a survey questionnaire and an in-depth interview. The data was analyzed by using mean, standard deviation, Principal-Component Analysis (PC), and Varimax Orthogonal Rotation Method. The results of the study showed that this educational management model consisted of a set of objectives, processes, and methods for joint planning, implementing, and evaluating educational management for equality and equality. The main component of the model was the role of participation of the school board in the 3 primary tasks of the school and 19 more sub-components. This model came with the highlight of the model was the emphasis on individual learners, systematically exploration of the needs and problems of each person. This model has been evaluated by experts to be accurate, practical, and useful at the highest level.